Creating a physical biology : the Three-Man Paper and early molecular biology - Zimmer, Karl Günter, 1911-1988; Delbrück, Max; Sloan, Phillip R.; Fogel, D. Brandon; Timofeev-Resovskiĭ, N. V. (Nikolaĭ Vladimirovich), 1900-1981 (University of Chicago Press, 2011)
In 1935 geneticist Nikolai Timof̌eff-Ressovsky, radiation physicist Karl G. Zimmer, and quantum physicist Max Delbruck published & ldquo;On the Nature of Gene Mutation and Gene Structure, & rdquo; known subsequently as the & ldquo;Three-Man Paper. & rdquo; This seminal paper advanced work on the physical exploration of the structure of the gene through radiation physics and suggested ways in which physics could reveal definite information about gene structure, mutation, and action. Representing a new level of collaboration between physics and biology, it played an important role in the b.